MAKNA KETERASINGAN DAN CITRAAN DALAM KUMPULAN PUISI ETSA KARYA TOTO SUDARTO BACHTIAR - SUHARTINI SUHARTINI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
Theme and imagery are two elements that are part of the unified structure of poetry. In Etsa, a collection of poems by Toto Sudarto Bachtiar, the themes used mostly imply alienation and pessimistic tones, but contain religious content. The use of imagery has an appropriate and strong carrying capacity for poetry, so that the reader can be led to feel what the poet is feeling. The purpose of this research is to describe the meaning of alienation and the carrying capacity of imagery to the contents of the poem. This study uses qualitative analysis techniques. The sample in this study was taken from the population in the form of Toto Sudarto Bachtiar's poems in the collection of Etsa poems. The discussion of the problem uses two approaches to literary works, namely structural and semiotic approaches. The results of the study can be concluded that the most dominant meaning of alienation in the collection of Etsa poems by Toto Sudarto Bachtiar is the theme of death, the theme of solitude, the theme of suffering, and the theme of depression. The most frequently used types of imagery are auditory imagery (in the theme of death), visual imagery (in the theme of depression), auditory imagery (in the theme of death), auditory and moving imagery (in the theme of suffering), auditory and moving imagery (in the theme of solitude). . The use of imagery in the collection of Etsa poems by Toto Sudarto Bachtiar has two effects, namely clarifying the description of the atmosphere and strengthening the description of the meaning of words, thereby helping to understand the meaning of the poem. ABSTRAKTema dan citraan merupakan dua unsur yang menjadi bagian dari kesatuan struktur pembentuk puisi. Dalam Etsa, kumpulan puisi karya Toto Sudarto Bachtiar unsur tema yang digunakan sebagian besar menyiratkan makna keterasingan dan nada pesimistis, namun terkandung muatan religius di dalamnya. Penggunaan citraan mempunyai daya dukung sesuai dan kuat terhadap puisi, sehingga pembaca dapat tertuntun ikut merasakan apa yang dirasakan penyair.Tujuan penelitian ini untuk mendeskripsikan makna keterasingan dan daya dukung citraan terhadap isi puisi. Penelitian ini menggunakan teknik analisis kualitatif. Sampel dalam penelitian ini diambil dalam populasi berupa puisi-puisi Toto Sudarto Bachtiar dalam kumpulan puisi Etsa. Pembahasan masalah menggunakan dua pendekatan karya sastra, yaitu pendekatan struktural dan semiotik. Hasil penelitian dapat disimpulkan bahwa makna keterasingan yang paling dominan dalam kumpulan puisi Etsa karya Toto Sudarto Bachtiar adalah tema kematian, tema kesunyian, tema penderitaan, dan tema kemurungan. Jenis citraan yang paling sering digunakan adalah citraan pendengaran (dalam tema kematian), citraan penglihatan (dalam tema kemurungan), citraan pendengaran (dalam tema kematian), citraan pendengaran dan gerak (dalam tema penderitaan), citraan pendengaran dan gerak (dalam tema kesunyian). Penggunaan citraan dalam kumpulan puisi Etsa karya Toto Sudarto Bachtiar mempunyai dua efek, yaitu memperjelas gambaran suasanadan memperkuat gambaran arti kata, sehingga membantu pemahaman makna puisi.